Histological Study of Effect of Oral Administration of Monosodium Glutamate (MSG) on Duodenum of Wistar Rats - Rahayu, Mulyati Sri; Perwira Awaludin, Lambang Rizki; Wahyuni, Sri (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Monosodium glutamate (MSG) is a widely marketed flavor enhancer that is regularly consumed. MSG is toxic to several organs including the small intestine. Previous studies have reported the effects of high doses of MSG; however, these findings are not directly applicable to equivalent human intakes. This study aimed to investigate the effect of MSG on the duodenum in rats administered with human average daily intake (ADI). Twenty-four adult male Wistar rats weighing 150-250 g at the age of 8-12 weeks were divided into four experimental groups (n = 6): normal control group (C), group 1 (0.378 mg/g b.wt), group 2 (0.756 mg/g b.wt), and group 3 (1.512 mg/g b.wt) oral MSG per day for 21 days. Duodenaltissue was dissected and stained with hematoxylin and eosin (HE) for histological examination. Data analysis was performed using the Kruskal-Wallis test (p < 0.05). The average height of the villus was calculated for each group: control (1047.40 ± 158.0 µm), Group 1 (850.68 ± 202.38 µm), Group 2 (906.29 ± 416.63 µm), and Group 3 (877.55 ± 154.65 µm). There was a difference in the height of the villi between all groups; however, there was no statistically significant difference compared with the control group (p = 0.384). The control group showed a normal appearance of the duodenal mucosa without inflammatory cells. In contrast, the treatment group showed inflammatory cell infiltration and lacked distinct brush-border structures. Our study showed that administration of MSG at an estimated dose of human ADIresulted in histological damage to the duodenum.